Literasi Keuangan : Pengaruh Usia dan Jumlah Anggota Keluarga Petani Kopi di Aceh Tengah - Risnafitri, Hafizhah (JURNAL AGRICA, 2025)
This study aims to analyze the influence of age and the number of family members on the financial literacy of coffee farmers in Central Aceh Regency. Financial literacy is regarded as a crucial ability for farmers in managing income and financial planning, particularly in facing coffee price fluctuations and the risk of household economic instability. This research employed a quantitative approach with a survey method on 105 coffee farmer respondents selected through a purposive sampling technique. The research instrument was a questionnaire adapted from the OECD/INFE Toolkit to measure three dimensions of financial literacy: financial knowledge, financial behavior, and financial attitude. Data analysis was conducted using non-parametric statistical tests. The results show that age has a significant negative effect on the financial literacy of coffee farmers in Central Aceh, meaning that as age increases, the level of financial literacy tends to decrease. Conversely, the number of family members was found to have no significant influence on financial literacy. These findings provide important implications for the design of financial education programs that focus on older age groups in rural areas, in order to enhance financial independence and the sustainability of coffee farming.